DNA methylation of the Rtl1 promoter in the placentas with fetal growth restriction - Kazumichi Fujioka; Kosuke Nishida; Mariko Ashina; Shinya Abe; Sachiyo Fukushima; Toshihiko Ikuta; Shohei Ohyama; Ichiro Morioka; Kazumoto Iijima (Elsevier, 2019)
Background: Small for gestational age (SGA) babies experience fetal growth restriction because of placental insufficiency, and aberrant fetal growth has been linked to DNA methylation in the placenta. An imprinted gene encoding retrotransposon-like protein 1 (RTL1) is regulated by DNA methylation in the promoter region and plays a key role in placental development. We therefore investigated the DNA methylation status of RTL1 in the placenta of infants with severe SGA. Methods: We extracted DNA from the placenta of appropriate for gestational age (AGA; gestational age 35 ± 6 weeks, birthweight 2292 ± 1006 g; n = 12), SGA (birthweight z-score ≤−2 SD, 33 ± 5 weeks, 1373 ± 580 g; n = 11), and severe SGA (birthweight z-score ≤−3 SD, 33 ± 4 weeks, 1145 g ± 423 g; n = 7) infants, and we determined the methylation rates of five CpG sites in the CG4 (82,275,427-82,275,737 in NT_026437 sequence, NCBI database) region of the RTL1 promoter by pyrosequencing. We defined hypermethylation (>75.5%) and hypomethylation (<45.6%) based on the average methylation rate exceeding ± two standard deviations (SD) in the AGA group, respectively, and compared these among groups. Results: There was no significant difference in the average methylation of CpG1-5 (control 59%, SGA 60%, severe SGA 63%), but abnormal methylation (hyper-/hypo-methylation) in CpG1 differed significantly among the groups (control 0%, SGA 36%, severe SGA 71%). Conclusion: Infants with severe SGA have abnormal placental DNA methylation of CpG1 in the CG4 region of RTL1, suggesting the existence of disturbed epigenetic control in utero. Key Words: pregnancy, intrauterine growth restriction, methylation